2015
DOI: 10.2474/trol.10.428
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on the Tribological Properties of Palm Kernel Activated Carbon-Epoxy Composite

Abstract: The aim of this study was to investigate the effect of temperature on the tribological properties of Palm Kernel Activated Carbon-Epoxy (PKAC-E) composite. All specimens were formed into 10 mm diameter pins of 30 mm length, using a hot compaction technique. Tribological testing was carried out using a pin-on-disc tribometer in dry sliding conditions by applying temperatures in the range of 27°C to 150°C, at constant sliding speed, applied load, and sliding distance. The results showed that both coefficient of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Many researchers have investigated the temprature on the wear and frictional behaviour of polymers. For instance, Tahir et al [9] studied the effect of the operating temperature on the tribological behaviour of carbon fibre composites with a different epoxy system. They reported that the temperature has a high influence on the COF behaviour, and a drastic increase in the COF was reported at 90 ℃, below the glass transition temperature (Tg) of the epoxy, 100 ℃ [31].…”
Section: Frictional Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have investigated the temprature on the wear and frictional behaviour of polymers. For instance, Tahir et al [9] studied the effect of the operating temperature on the tribological behaviour of carbon fibre composites with a different epoxy system. They reported that the temperature has a high influence on the COF behaviour, and a drastic increase in the COF was reported at 90 ℃, below the glass transition temperature (Tg) of the epoxy, 100 ℃ [31].…”
Section: Frictional Behavioursmentioning
confidence: 99%
“…Unlike metals, the wear performance of polymers is very sensitive to the operating temperature, i.e., the induced heat at the contact zone during the wear process. In tribological applications of polymers, one main parameter to be considered during the wear process is how the generated heat of the rubbing process affects the tribological components' mechanical and wear performances [9][10][11]. Interface temperature may deteriorate these components' mechanical properties by reducing the hardness and the stiffness, and it can break the polymer bonds, resulting in a higher wear rate and a higher coefficient of friction (COF) for components [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Pertaining to the previous study by Kaggwa et al 23) , activated carbon in nanofluid has significantly increased the lubricant viscosity and improved the heat transfer efficiency. Furthermore, Ayuma et al 24) found that the activated carbon generated a tribofilm between two contact surfaces thus prevented wear and friction during the pin-on-disc test. The carbon-based tribofilm adhered at the contact surfaces which prohibited the adhesion to occur.…”
Section: Introductionmentioning
confidence: 99%
“…There are still few studies on natural fiber as a friction material. Some research has been conducted using the powdered form of natural fiber (sugarcane fiber [13], banana peel [14], palm kernel [15], and periwinkle cells [16]) for friction material. This article discusses the development of cantala fiber in the form of short fibers as the reinforcement material for the friction brake composite.…”
Section: Introductionmentioning
confidence: 99%